Complexity of Chronic Conditions' Impact on End-of-Life Expense Trajectories of Medicare Decedents. (November 2017) - Sullivan, Suzanne S.; Li, Junxin; Wu, Yow-Wu Bill; Hewner, Sharon
Abstract : OBJECTIVE: The aim of this study is to determine if the pattern of monthly medical expense can be used to identify individuals at risk of dying, thus supporting providers in proactively engaging in advanced care planning discussions. BACKGROUND: Identifying the right time to discuss end of life can be difficult. Improved predictive capacity has made it possible for nurse leaders to use large data sets to guide clinical decision making. METHODS: We examined the patterns of monthly medical expense of Medicare beneficiaries with life-limiting illness during the last 24 months of life using analysis of variance, t tests, and stepwise hierarchical linear modeling. RESULTS: In the final year of life, monthly medical expense increases rapidly for all disease groupings and forms distinct patterns of change. CONCLUSION: Type of condition can be used to classify decedents into distinctly different cost trajectories. Conditions including chronic disease, system failure, or cancer may be used to identify patients who may benefit from supportive care.